Ionospheric Drift Motions and Velocities at UTHM’s Parit Raja Station During Periods of Low Solar and Geomagnetic Activities - Ahmad, Abdull Zubi; Mohd Zain, Ahmad Faizal; Nagarajoo, Karthigesu (International Journal of Integrated Engineering, 2022)
Measurements relating to ionospheric plasma drift have been made by the Wireless and Radio Science Centre (WARAS) at Universiti Tun Hussein Onn Malaysia (UTHM) Parit Raja station in Batu Pahat, Johor, since 2004. This is done using a digital doppler interferometer which allows investigations into the dynamics of the ionosphere at this equatorial station to be carried out. These measurements include Doppler shifts and angles of arrival of the reflected HF signals that also allows simultaneous determination of plasma drift directions, drift distance covered and velocities as well as virtual heights of reflection, from ionospheric scattering point sources embedded within the moving plasma. By employing Doppler inteferometry reception technique at four receivers connected to four square array antennas nearby, it is possible to identify the locations, movements and velocities of the bulk scattering points reflected from the ionospheric F-region from the vertically incident HF waves. These waves are transmitted at frequencies of 6MHz, 7MHz, and 8MHz which cover the local F-layers since the critical frequencies lie between 5.9MHz and 8MHz. This work is based on data collected from the F2-layer of this local station at about 300km of virtual height during the measurement period of 2005.